2014
DOI: 10.1111/jre.12221
|View full text |Cite
|
Sign up to set email alerts
|

Non‐surgical periodontal therapy with systemic antibiotics in patients with untreated chronic periodontitis: a systematic review and meta‐analysis

Abstract: Systemic antibiotics combined with SRP offer additional clinical improvements compared to SRP alone. Although there were no statistically significant differences, there was a trend that for initially moderate and deep pockets, metronidazole or metronidazole combined with amoxicillin, resulted in clinical improvements that were more pronounced over doxycycline or azithromycin. Additionally, there was a trend that the magnitude of the clinical benefit became smaller over time (1 year).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
147
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(161 citation statements)
references
References 110 publications
11
147
1
2
Order By: Relevance
“…Given smokers are among the most difficult periodontal patients to treat, in terms of limited improvements following therapy, the use of systemic antibiotics can be considered of benefit in this group of susceptible patients [23]. The results of a recent meta-analysis support the additional effect of the usage of systemic antibiotics, which could be explained by delayed microbial infection, better infection control and improved periodontal healing because these antibiotics support the immune system by suppressing the target microbial species [24]. Matarazzo et al [25] suggested a clear benefit of the use of systemic antibiotics in the microbial profile of smoker subjects at 3 months after periodontal therapy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Given smokers are among the most difficult periodontal patients to treat, in terms of limited improvements following therapy, the use of systemic antibiotics can be considered of benefit in this group of susceptible patients [23]. The results of a recent meta-analysis support the additional effect of the usage of systemic antibiotics, which could be explained by delayed microbial infection, better infection control and improved periodontal healing because these antibiotics support the immune system by suppressing the target microbial species [24]. Matarazzo et al [25] suggested a clear benefit of the use of systemic antibiotics in the microbial profile of smoker subjects at 3 months after periodontal therapy.…”
Section: Discussionmentioning
confidence: 97%
“…Matarazzo et al [25] suggested a clear benefit of the use of systemic antibiotics in the microbial profile of smoker subjects at 3 months after periodontal therapy. However, one should take into account that the widespread use of systemic antibiotics in periodontology might lead to bacterial resistance in the long term, besides the difficulty to achieve a therapeutic concentration in the gingival crevice fluid, an increased risk of adverse drug reactions and uncertain patient compliance [7,8,24]. Moreover, the results of a recent clinical trial confirm that smokers respond less favorably to periodontal therapy, since even the adjunctive use of metronidazole and amoxicillin was not as effective for the treatment of smokers [26].…”
Section: Discussionmentioning
confidence: 99%
“…(13,16) Estos resultados se pueden explicar debido a que la composición de la microflora subgingival difiere notablemente entre pacientes y grupos étnicos y geográficos. (7,8) La comprensión de la forma como se organiza y cambia la flora microbiana subgingival en la PAgG promueve la elección de terapias antibióticas adjuntas a la terapia mecánica; antimicrobianos como la azitromicina o la doxiciclina sin efectos importantes sobre la flora subgingival no se deben contemplar para el tratamiento en pacientes con este tipo de periodontitis, (18,19) por el contrario terapias como amoxicilina y metronidazol, (20) o la más recientemente propuesta moxifloxacina, (21) muestran una eficacia importante en el manejo coadyuvante farmacológico de la PAgG. Diferentes reportes muestran la presencia de bacilos entéricos gram-negativos en bolsas de pacientes diagnosticados con periodontitis, (22,23) en nuestro estudio 10% de los pacientes presentaron resultado positivo para estos microorganismos, lo que confirma la participación de bacilos entéricos en la conformación del ecosistema de la periodontitis, sin embargo no se ha esclarecido el papel de ellos en la patogenia de la enfermedad.…”
Section: Sas ( Mm±sd ) 32%unclassified
“…While the use of azithromycin can be an effective adjunctive treatment modality, a concern has been raised regarding the increased incidence of bacterial resistance to macrolides including azithromycin [5,6]. The use of metronidazole alone or in combination with amoxicillin may be one of the most potent antimicrobial therapies for periodontitis including aggressive periodontitis [7]. However, the use of metronidazole is not indicated for the treatment of periodontitis in Japan.…”
Section: Introductionmentioning
confidence: 98%